Implementasi Model Edukasi Interaktif Sebagai Sarana Pengembangan Karakter Anak di LKSA Sabilul Muhtadien - Cindya Alfi; Afifatul Izzatil Husna; Deni Tri Lutfiana; Elsa Nadya Ulandari; Fatqul Anang Ma’ruf; Julia Masrifatin; Li’ana Turosidah; Muhammad Amiqul Ilmi; Muhammad Tegar Amru; Putri Ayu Maharani; Putri Nanda Sholikah; Slamet Supriadi; Tsaniatul Muyassaroh; Vitika Kurniawati; Widya Putri Mailani (Lembaga Pengembangan Kinerja Dosen, 2025)
Children in orphanages often face unique challenges in character formation due to limited educational stimulation and diverse social interactions, despite their basic needs being met. The interactive education model applied in the